Validitas dan Praktikalitas Bahan Ajar Mengintegrasikan STL (Sains, Teknologi dan Lingkungan) pada Edmodo Materi Fluida Statik dan Dinamik Kelas XI SMA - Wenni Tiarasari; Akmam Akmam; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2018)
Learning materials are references that contain information systematically arranged. In fact of the school, learning materials that created by teachers has not been integrating physics learning with other science and application of physics in technology in everyday life. One of the solutions to solve this problem is to create learning materials that integrate Science, Technology and Environment (STE) in learning Physics with ICT through problem-oriented learning models. This study aims to produce teaching materials to integrate Edmodo based on STL model Problem-Based Instruction that static and dynamic fluid materials with a good description, valid and practical. The research conducted that include the types of research and development (R&D) using the 4-D development model  which reduced to 3-D with defining, designing, and developing phases. The subjects of this research were 3 respondens who are validators of physic lecturer in Faculty of Mathematics Natural Sciences State University of Padang, 2 physics teachers and 31 students of SMAN 1 Padang. The object of this research is to integrate the materials Science, Technology and the Environment of learning materials to integrate SLT based on the model of Edmodo Problem-Based Instruction materials static and dynamic fluid. Based on this research, it has produced some products. First, learning materials product that integrate edmodo-based on STL model Problem-Based Instruction materials static and dynamic fluid. Second, learning materials product that integrate STL-based valid categories are on Edmodo with an average score of 80%. Third , teaching materials product integrate STL-based on practical categories are on Edmodo according to the teachers with a result of 86.25%, while according to the student's learning materials integrate STL-based practical categories are on Edmodo with an average score of 83,93%.